Peranan Punishment pada Santriwati dalam Manajemen Kesiswaan (Studi Kasus di Pondok Pesantren Al Husna) - Elvi Azizah; Nasrul Syakur Chaniago (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: The topic of this research is " The Role of Punishment for Female Students in Student Management (Case Study at Al Husna Islamic Boarding School)". This research aims to describe the application of discipline in the management of santri through educational punishment at the Al-Husna Islamic Boarding School, understand the stages of punishment given at school, and determine the factors that support or hinder the improvement of santri discipline through education. punishment. The location of this research is at the Al-Husna Marindal 1 Patumbak Deli Serdang Islamic Boarding School educational institution, which is an educational institution founded on April 17 1988 M/11 Ramadhan 1409 H and is one of the competent Islamic educational institutions. In this research, the researcher used a qualitative approach with a case study research type and was descriptive in nature. The aim of giving punishment is to prevent children from repeating actions that are not permitted. The role of parenting is to warn female students not to repeat themselves and explain the reasons why this is not allowed. The punishment given to female students at the Al-Husna Islamic boarding school has been given evenly and in balance according to the area that the female student violated.Keywords: Student Management, Islamic Boarding School, Punishment Abstrak: Topik penelitian ini tentang “Peranan Punishment pada Santriwati dalam Manajemen Kesiswaan (Studi Kasus di Pondok Pesantren Al Husna)”. Penelitian ini bertujuan untuk mendeskripsikan penerapan disiplin dalam pengelolaan santri melalui hukuman pendidikan di Pondok Pesantren Al-Husna, memahami tahapan hukuman yang diberikan di sekolah, dan mengetahui faktor-faktor yang mendukung atau menghambat peningkatan kedisiplinan santri melalui pendidikan hukuman. Lokasi penelitian ini bertempat di lembaga pendidikan Pondok Pesantren Al-Husna Marindal 1 Patumbak Deli Serdang yang merupakan lembaga pendidikan yang didirikan pada 17 April 1988 M/11 Ramadhan 1409 H dan merupakan salah satu lembaga pendidikan islam yang kompeten. Dalam penelitian ini peneliti menggunakan pendeketan kualitatif dengan jenis penelitian case study research (studi kasus) dan bersifat deskriptif. Pemberian punishment ini bertujuan agar anak tidak mengulangi perbuatan yang tidak diperbolehkan. Peran pengasuhan untuk memperingatkan santriwati agar tidak mengulangi serta menjelaskan alasan sebab akibat hal tersebut tidak di perbolehkan. Pemberian punishment pada santriwati di pondok pesantren al-husna sudah diberikan dengan merata dan seimbang sesuai bidang bagian yang di langgar santriwati. Kata kunci: Manajemen Kesiswaan, Pondok Pesantren, Hukuman